2022
DOI: 10.1101/2022.10.11.511741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune-modulatory effects of low dose γ-radiation on wax moth (Galleria mellonella) larvae

Abstract: Larvae of the greater wax moth Galleria mellonella are common pests of beehives and commercial apiaries, and in more applied settings, these insects act as alternative in vivo bioassays to rodents for studying microbial virulence, antibiotic development, and toxicology. In the current study, our overall aim was to assess the putative adverse effects of background gamma radiation levels on G. mellonella. To achieve this, we exposed larvae to low (0.014 mGy/h), medium (0.056 mGy/h), and high (1.33 mGy/h) doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 73 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…Again, this is consistent with data from human studies which showed that UVB irradiation of the human body led to decreases in both phagocytic, chemotactic and adhesion activities of neutrophils, largely due to decreased expression of receptors involved in such processes (Lundin et al, 1990;Leino et al, 1999;Hart and Norval, 2021). This further establishes the synonymy of cellular innate immunity in G. mellonella and mammals, and that the former is a candidate model for reducing our reliance on mammals for such studies (Browne et al 2013;Kay et al 2019;Krachler et al, 2021;Lim et al, 2022). Therefore, while more haemocytes remain in larvae exposed to UVA, they were functionally compromised, whereas UVBradiated larvae had fewer haemocytes which was also compromised -which UVB is more potent an antagonist -as reflected in larval health, and expedited mortality when infected, in addition to compromised haemocyte functionality.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Again, this is consistent with data from human studies which showed that UVB irradiation of the human body led to decreases in both phagocytic, chemotactic and adhesion activities of neutrophils, largely due to decreased expression of receptors involved in such processes (Lundin et al, 1990;Leino et al, 1999;Hart and Norval, 2021). This further establishes the synonymy of cellular innate immunity in G. mellonella and mammals, and that the former is a candidate model for reducing our reliance on mammals for such studies (Browne et al 2013;Kay et al 2019;Krachler et al, 2021;Lim et al, 2022). Therefore, while more haemocytes remain in larvae exposed to UVA, they were functionally compromised, whereas UVBradiated larvae had fewer haemocytes which was also compromised -which UVB is more potent an antagonist -as reflected in larval health, and expedited mortality when infected, in addition to compromised haemocyte functionality.…”
Section: Discussionsupporting
confidence: 84%
“…The copyright holder for this preprint this version posted December 2, 2022. ; https://doi.org/10.1101/2022.12.02.517514 doi: bioRxiv preprint Kay et al 2019;Krachler et al, 2021;Lim et al, 2022). Therefore, while more haemocytes remain in larvae exposed to UVA, they were functionally compromised, whereas UVBradiated larvae had fewer haemocytes which was also compromised -which UVB is more potent an antagonist -as reflected in larval health, and expedited mortality when infected, in addition to compromised haemocyte functionality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations